Adaptation to climate change on rice cultivation in the marginal coastal land through optimizing soil ameliorant application. Issue 1 (July 2021) - Kusumarini, N; Nugroho, G A; Adella, N D; Indahsari, D N; Syaadah, L Z; Hasanah, U; Kurniawan, S
Abstract: Global warming has widely impact on increasing sea water level, resulting in high soil salinity in the agricultural coastal land. As consequence, rice productivity in Coastal land may decrease due to soil salinity disrupt plant physiological processes. The study aimed to analyze the impact of ameliorants application on plant and soil in rice cultivation. The study was conducted in coastline land, locating at 750 m from the Java Sea. The land was treated with several types of soil ameliorant (dolomite, agricultural lime) under dosage 1000 kg ha −1 as a control, and several dosages of gypsum ranged between 500 kg ha −1 to 2000 kg ha −1 . Soil ameliorants were significantly increased nutrient uptake by the plant, resulting in increases of biomass up to 42.8% compared to control in the treatment of 1000 kg ha −1 dolomite. This was probably due to the application of soil ameliorants decreased salinity level by lowering pH by 4-5%; EC by 42-57%; Na by 39.1%; and Cl by 12.2%. Improving soil nutrient content was reached by applying 1000 kg ha −1 gypsum which increases total N by 5 – 25%; Ca by 5%, and S by 28% compared to control and increased another soil nutrient content compared to before treatments.